Analysis of Maternal Figure Resilience in Islamic Literature onChildren’s Character Formation Through Spiritual Parenting - Faiqotus Nabila; Samsimah; Saepul Malik; Benny Prasetiya (Al-Hikmah: International Journal of Islamic Studies, 2026)
Social transformation in the modern era, driven by rapid digital technological development, individualistic lifestyles, and weakened emotional interaction within families, has contributed to various moral and psychological problems among children.In this context, the family, especially the mother, plays a central role in shaping children’s character through the internalisation of spiritual and moral values. This study aims to analyse the concept of maternal resilience in Islamic literature, examine the principles of spiritual parenting, and identify their relevance to children’s character formation in contemporary society. The research employs a qualitative approach using library research and a contextual hermeneutic method to interpret values derived from the Qur’an, hadith, and Islamic educational literature. Data analysis was conducted through data reduction, thematic categorisation, hermeneutic interpretation, and conceptual synthesis. The findings reveal that maternal resilience in Islam is understood not only as the ability to cope with life’s challenges but also as spiritual endurance rooted in the values of ṣabr (patience), tawakal (trust in God), gratitude, compassion, and sincerity. These values form the foundation of spiritual parenting, enabling the development of religious, adaptive, empathetic, and morally virtuous children amidst the challenges of modernity.